Enhancing the machining productivity in PMEDM for titanium alloy with low-frequency vibrations associated with the workpiece - Le Quang Dung; Huu Phan Nguyen; Van Dua Tran; Van Thien Nguyen; Thangaraj Muthuramalingam (Journal of the Mechanical Behavior of Materials, 2024)
The incorporation of frequency vibration into the powder mixed electric discharge machining (PMEDM) process has the potential to significantly enhance the productivity and quality of the machining process, as well as to provide a great deal of opportunities in this sector. An analysis and evaluation of the machining productivity (material removal rate [MRR]) in PMEDM with low-frequency vibration was carried out in this work by considering SKD61 as a workpiece. The oil dielectric solution mixed with titanium powder was used as a dielectric medium with red copper (Cu) as the electrode. At this point in time, the process technology parameters that have been chosen for inquiry are as follows: current (I), pulse on time (T on), powder concentration (C p), P, F, and A. The Taguchi technique (L25) was used to create the experimental matrix. With the use of analysis of variance, it was able to examine the impact that the factors had on MRR, and the analysis was utilized to ascertain the highest possible value of MRR. I was the parameter that has the most significant effect, according to the findings, whereas T on was the parameter that has the least significant effect. The maximum value of the MRRmax is equal to 31.29 mm3/min.